Efeitos interfaciais na formação de domínios magnéticos e skyrmions em multicamadas com anisotropia magnética perpendicular - Dugato, Danian Alexandre (2021)
Ferromagnet/heavy metal multilayers can exhibit perpendicular magnetic anisotropy (AMP), high density of magnetic domain, and skyrmions. These structures have great potential for applications in magnetic recording media and logic gates. The characteristics of the magnetic domains and skyrmions depend on the multilayer magnetic properties, which can be adjusted by modifying the sample structure. The properties of multilayers are mainly dependent on the interfacial effects that occur between the ferromagnet and the heavy metal. Among the most relevant effects are AMP, the Dzyaloshinskii-Moriya interaction (DM) and the magnetic proximity effect (EPM). The general objective of this thesis is to analyze the impact of these effects in the magnetic properties and in the magnetic domain formation, seeking improvements to obtain domains and skyrmions with potential for technological application. We adjusted the amplitudes and directions of these effects through interface engineering. We developed three independent systematic studies on multilayers based on Co and heavy metals such as Pt, W and Hf. We observed that high DM interaction values, together with AMP and saturation magnetization (Ms) reduction, provide the formation of patterns with high density of magnetic domains. In the case of sub-nanometric multilayers, there is a high magnetic polarization of the heavy metal by EPM due to the presence of high interfacial disorder. This also yields to a non-zero DM interaction, allowing the stabilization of isolated skyrmions at zero magnetic field in nominally symmetric multilayers. Using negative EPM materials, we were able to reduce Ms by up to 70 %, preserving the AMP and the magnetic domains and skyrmions formation. We conclude that the adjustment of interfacial effects is necessary and decisive for the improvement of magnetic properties and the formation of magnetic domains and skyrmions.